Uvajanje načel transparentnost v delo javne uprave - Demšar, Franci (Družboslovne razprave, 2008)
In the majority of contemporary societies knowledge is an important policy priority. At the same time, transparency is an ideal in most developed political environments. In the article the authors focus on an analysis of the elements of transparency in the context of public policies. They focus on science policy where they see transparency as a tool for fostering research quality. Through a case study of the Slovenian Research Agency they present the importance of information technologies in the process of ensuring such transparency. They conclude that the inclusion of modern information technologies, which reduce the monopoly over information and its interpretation, forms a basis for greater efficiency in the scientific field. By objectifying the evaluation criteria some traditional presumptions about research activities are challenged, and this in turn leads to greater transparency and consequently to higher scientific quality. The authors stress the concept of transparency as being tool for enhanced efficiency, which based on the mutual control of all actors involved in a particular process.
Keywords: Javna agencija za raziskovalno dejavnost Republike Slovenije; Science policy; Public policy; Znanstvena politika; Scientific research; Javna politika; Quality; scientific method; Znanstveno raziskovanje; Evaluation; Kakovost; Vrednotenje; Slovenia; Slovenija; ARRS; Association of Road Racing Statisticians